The distribution of Mola alexandrini in the Subtropical Eastern Atlantic, with a note on Mola mola - Wirtz, Peter (2020)
he presence of the “Bump-head sunfish” Mola alexandrini (Ranzani 1839) is recorded, via photographic evidence, from the Azores, Madeira Island, the Canary Islands, and the Cape Verde Islands. Eastern Atlantic individuals of Mola mola can also have a bump on the head.